Pola Penjualan Gelang Gemstone Menggunakan Algoritma FP-Growth Pada CV. Samapura Jewelry - Ivan Kurniawan Sentosa; I Putu Satwika; Ketut Queena Fredlina (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
In the continuously evolving era like the present, competition among other businesses also undergoes significant changes. Therefore, this company needs to enhance its sales strategy to remain relevant, dominant, and profitable. In this context, advancements in the field of technology can provide substantial assistance in the development of sales strategies. By utilizing customer transaction data, CV. Samapura Jewelry can perform data mining and apply the FP-Growth algorithm to identify association patterns among different types of bracelets. This will help the company to understand the current trends in bracelet preferences and enable collaborations between different bracelet types. Through the calculations, the company will obtain recommendations for optimal bracelet sales combinations. Based on the research findings, it was discovered that one of the bracelet sales packages with the highest support and confidence levels is the Crystal Red Nugget Bracelet Gold and Crystal Rainbow Nugget Bracelet Silver in relation to the Crystal Rainbow Nugget Bracelet Gold. This package has a support value of 0.31% and a confidence of 75%. This research is highly significant for CV. Samapura Jewelry as it will provide valuable insights in developing an effective sales strategy. By leveraging the FP-Growth algorithm and data analysis, the company can enhance its product offerings to align with market trends and improve customer satisfaction. Thus, the company can maintain its presence in a competitive market and achieve long-term success